Regional citrate anticoagulation in cardiac surgery patients at high risk of bleeding: a continuous veno-venous hemofiltration protocol with a low concentration citrate solution - Morabito, Santo (BioMed Central, 2012)
INTRODUCTION: Regional citrate anticoagulation (RCA) is a valid option in patients at high risk of bleeding who are undergoing continuous renal replacement therapy (CRRT). The aim of this study was to evaluate, in critically ill patients with severe acute kidney injury following cardiac surgery, the efficacy and safety of RCA-continuous veno-venous hemofiltration (CVVH) using a low concentration citrate solution. METHODS: In high bleeding-risk cardiac surgery patients, we adopted, as an alternative to heparin or no anticoagulation, RCA-CVVH using a 12 mmol/l citrate solution. For RCA-CVVH settings, we developed a mathematical model to roughly estimate citrate load and calcium loss. In order to minimize calcium chloride supplementation, a calcium-containing solution was used as post-dilution replacement fluid. Statistical analysis was performed using the Student t-test or analysis of variance (ANOVA) with post-hoc tests, Wilcoxon or Kruskal-Wallis tests for non-parametric analysis, and Kaplan-Meier survival analysis with Log Rank test. RESULTS: Thirty-three patients (age 70.8 ± 9.5, Sequential Organ Failure Assessment (SOFA) score 13.9 ± 2.5) were switched to RCA-CVVH from no anticoagulation CRRT. Among them, 16 patients had been previously switched from heparin to no anticoagulation because of bleeding or heparin-related complications. RCA-CVVH filter life (49.8 ± 35.4 hours, median 41, 152 circuits) was significantly longer (P < 0.0001) when compared with heparin (30.6 ± 24.3 hours, median 22, 73 circuits) or no anticoagulation (25.7 ± 21.2 hours, median 20, 77 circuits). Target circuit and systemic Ca(++ )were easily maintained (0.37 ± 0.09 and 1.18 ± 0.13 mmol/l), while the persistence of a mild metabolic acidosis required bicarbonate supplementation (5.8 ± 5.9 mmol/hours) in 27 patients. The probability of circuit running at 24, 48, 72 hours was higher during RCA-CVVH (P < 0.0001), with a lower discrepancy between delivered and prescribed CRRT dose (P < 0.0001). RCA was associated with a lower transfusion rate (P < 0.02). Platelet count (P = 0.012) and antithrombin III activity (P = 0.004) increased throughout RCA-CVVH, reducing the need for supplementation. CONCLUSIONS: RCA safely prolonged filter life while decreasing CRRT downtime, transfusion rates and supplementation needs for antithrombin III and platelets. In cardiac surgery patients with severe multiple organ dysfunction syndrome, the adoption of a 12 mmol/l citrate solution may provide a suboptimal buffers supply, easily overwhelmed by bicarbonate supplementation.